THE ROLE AND IMPORTANCE OF THE OLYMPIAD IN THE TRAINING OF MATHEMATICS SPECIALISTS - Sattorov Ermamat Norqulovich; Boyqobilov Erali Bahromjon o‘g‘li, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This paper examines the role and significance of the Mathematics Olympiad in the training of future mathematicians. The idea that the mathematical Olympiad is an important part of the educational process at a university is grounded.